Effects of ebselen addition on emotional processing and brain neurochemistry in depressed patients unresponsive to antidepressant medication - Ramli, FF; Singh, N; Emir, UE; Villa, LM; Waters, S; Harmer, CJ; Cowen, PJ; Godlewska, BR (Springer Nature [academic journals on nature.com], 2024)
Lithium is an effective augmenting agent for depressed patients with inadequate response to standard antidepressant therapy, but numerous adverse effects limit its use. We previously reported that a lithium-mimetic agent, ebselen, promoted a positive emotional bias—an indicator of potential antidepressant activity in healthy participants. We therefore aimed to investigate the effects of short-term ebselen treatment on emotional processing and brain neurochemistry in depressed patients with inadequate response to standard antidepressants. We conducted a double-blind, placebo-controlled 7-day experimental medicine study in 51 patients with major depressive disorder who were currently taking antidepressants but had an inadequate response to treatment. Participants received either ebselen 600 mg twice daily for seven days or identical matching placebo. An emotional testing battery, magnetic resonance spectroscopy and depression and anxiety rating scales were conducted at baseline and after seven days of treatment. Ebselen did not increase the recognition of positive facial expressions in the depressed patient group. However, ebselen increased the response bias towards fear emotion in the signal detection measurement. In the anterior cingulate cortex, ebselen significantly reduced the concentrations of inositol and Glx (glutamate+glutamine). We found no significant differences in depression and anxiety rating scales between visits. Our study did not find any positive shift in emotional bias in depressed patients with an inadequate response to antidepressant medication. We confirmed the ability of ebselen to lower inositol and Glx in the anterior cingulate cortex. These latter effects are probably mediated through inhibition of inositol monophosphatase and glutaminase respectively.